Everyday Life Information Seeking Behaviour of New Muslim I mmigrants in Montreal - Alnaki, Hawa (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2018)
The study will examine the everyday life information seeking behavior of new Muslim immigrants in Montreal, as well as their information needs and the challenges they face. While there has been some work that focuses on the information needs and information seeking behavior of new immigrants in the United States, to date there has been little research within the Canadian context. Specifically, there is a failure to account for new Muslim immigrants' information needs in Montreal from the perspective of the library and information science field. Most information behavior research categorizes Muslim immigrants in Canada according to nationality or gender.